Transcription factor EB is involved in autophagymediated chemoresistance to doxorubicin in human cancer cells - FANG Li-mei; LI Bin; GUAN Jun-jie; XU Hai-dong; SHEN Gen-hai; GAO Quan-gen; QIN Zheng-hong (Acta Pharmacologica Sinica, 2017)
Transcription factor EB (TFEB) is a master regulator of autophagy activity and lysosomal biogenesis, but its role in autophagy-mediated cell survival and chemotherapy resistance is not completely understood. In this study, we explored whether TFEB played an important role in autophagy-mediated chemotherapy resistance in human cancer LoVo and HeLa cells in vitro. Treatment of human colon cancer LoVo cells with doxorubicin (0.5 μmol/L) induced autophagy activation and nuclear translocation of TFEB, which resulted from inactivation of the mTOR pathway. In both LoVo and HeLa cells, overexpression of TFEB enhanced doxorubicin-induced autophagy activation and significantly decreased doxorubicin-induced cell death, whereas knockdown of TFEB with small interfering RNA blocked doxorubicin-induced autophagy and significantly enhanced the cytotoxicity of doxorubicin. In LoVo cells, autophagy inhibition by 3-methyladenine (3-MA) or knockdown of autophagy-related gene Atg5 increased cell death in response to doxorubicin, and abolished TFEB overexpression-induced chemotherapy resistance, suggesting that the inhibition of autophagy made cancer cells more sensitive to doxorubicin. The results demonstrate that TFEB-mediated autophagy activation decreases the sensitivity of cancer cells to doxorubicin.